Mass Circumcision on Adult Students of Tribhuwana Tunggadewi University - Ka’arayeno, Arie Jefry; Choeron, Rachmat Chusnul (Journal of Community Service for Health, 2023)
This activity was a means to socialize the activities of the Center for Health Education Education and Community Welfare under the auspices of the UNITRI Research and Community Service Institute (LPPM) in collaboration with the Faculty of Health Sciences (FIKES) in this case the Department of Medical Surgical Nursing, as a vehicle for strengthening relationships within the UNITRI campus. with fellow academics, namely lecturers, staff and students. Through this activity, students could better understand the importance of health aspects and benefits as well as the importance of circumcision, even though circumcision can be done even though at the age of adult it was not a barrier to improving student health status. This activity was also a means for nursing students to provide practical experience and practice skills in the world of health, especially circumcision / circumcision. The mechanism of this activity was by registering 21 students and giving coupons to participate in this activity. This activity was carried out on Friday, July 5, 2019 to July 8, 2019. The name of the activity was the Health Checkup and Mass Circumcision with Tribhuwana Tunggadewi University. The types of activities were general checks such as measuring vital signs (blood pressure, weight, height), checking blood sugar levels, cholesterol, uric acid, and students getting free circumcision.